NORMATIVE PLAY TOWARD REDUCING FEAR INPRE-SCHOOL AGE CHILDREN AT DR. SLAMET HOSPITAL GARUT 2012 - Engkus Kusnadi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction. The fear experienced by a child aged 4-6 years who were hospitalized from a few things, namely the procedure to the patient, lack of adequate information, the foreign environment and with the development of son, the team of health care providers (doctors, nurses, laboratory personnel). Play is the work of a child, wherever they are playing is a necessity. The purpose of this study was to identify the influence of normative play on fear reduction pre-school children were hospitalized. Methods. This study used a quasi experimental with one group pre-post design on a sample of 24 pre-school children who were treated at the General Hospital dr. Slamet Garut. Fear experienced by children will be measured using an instrument Revised Child Medical Fear Scale was modified. Results. The results showed that the average (mean) scale fear before normative play (16.58) was higher than the average scale normative scared after play (7.75) at pre-school age children. The results of hypothesis testing using a pair t test produces p value of 0.0005 (<0.05). Normative play has significant effect in reducing the fear of pre-school children who were treated in dr. Slamet Garut hospital. Discussion. Therefore the child care room should be equipped with a playroom for the children who were treated and play therapy should be used as a standard operating procedure in reducing the fear of going to be the action of nursing and other health actions.  Keywords: normative play, fear, pre-school age children